Effect of video distraction on preoperative anxiety scores in pediatric patients undergoing general anesthesia in ophthalmic daycare procedures: A randomized controlled trial - Soumily Bandyopadhyay; Manpreet Kaur; Renu Sinha; Thilaka Muthiah; Arshad Ayub; Rajeshwari Subramaniam (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Parental separation, fear, and exposure to the operating room environment lead to stress and anxiety in pediatric patients. This study aims to identify the research gaps in the effect of video distraction on pediatric patients of Indian origin. We hypothesized that video distraction along with parental presence would reduce preoperative anxiety in pediatric patients undergoing ophthalmic procedures under general anesthesia compared with parental presence alone. Material and Methods: In this prospective randomized trial, 145 patients aged 2–8 years, ASA I-II, with at least one functional eye undergoing elective ophthalmic daycare procedures were enrolled. They were randomly allocated to two Groups: Group V had distraction by watching a video/playing a video game together with parental presence, whereas control Group C had parental presence alone without any video distraction. The primary objective of the study was to compare preoperative anxiety using the Modified Yale Preoperative Anxiety score (mYPAS) and heart rate (HR), whereas the secondary objective was to compare child fear, emergence delirium, and parental satisfaction between the two groups. The three time points for intergroup comparisons were the preoperative holding area 10 min before induction (T0), transport of the child to the operating room (T1), and face mask introduction (T2). Results: There was a statistically significant difference between mYPAS score in groups V and C at all time points (P = 0.036, P = 0.0001, P = 0.0000), parental satisfaction score at all three time points (P = 0.0049, P = 0.0000, P = 0.0000), and Child Fear Score at T1 and T2 (P = 0.0001, P = 0.0001, respectively). However, there was no statistically significant difference in the emergence of delirium between the two groups. Conclusions: Video distraction together with parental presence has a promising role for implementation in hospitals with heavy workload settings where pharmacological intervention would not be feasible, to alleviate preoperative anxiety in children. However, preoperative anxiety may not translate into increased postoperative emergence delirium as was earlier believed.